1989
DOI: 10.1002/em.2850140408
|View full text |Cite
|
Sign up to set email alerts
|

Biotesting of wastewater: A comparative study using the Salmonella and CHO assay systems

Abstract: Means to assess the toxicity of wastewaters are essential to implementing the Federal Clean Water Act. Health risk assessment based on single chemicals is limited by the number of chemicals that can be identified and to those chemicals for which toxicity data are available. Long-term whole animal tests on large numbers of wastewater samples are not practical. In this study, two short-term tests, the Salmonella mutagenicity assay and the Chinese hamster ovary (CHO) cell assay for mutagenicity and cytotoxicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
(3 reference statements)
0
9
0
1
Order By: Relevance
“…Another study conducted on the wastewater treatment plant which processes, notably, hospital wastewaters showed that the process used was effective in removing the genotoxicity (Jolibois and Guerbet, 2005b). However, for other hospitals and other wastewater treatment plants, it is not obvious that the genotoxic contamination disappears after treatment in the wastewater treatment plant, and thus this contamination could be found in drinking water (Waters et al, 1989;Doerger et al, 1992;Filipic and Toman, 1996). Since hospitals are one of the sources of rejections of genotoxic compounds in wastewater, efforts must be undertaken by hospitals in order to integrate the 195 Hospital wastewater genotoxicity knowledge and the control of their wastewaters, and thus the environment management, in the infection and environmental control programs.…”
Section: Resultsmentioning
confidence: 99%
“…Another study conducted on the wastewater treatment plant which processes, notably, hospital wastewaters showed that the process used was effective in removing the genotoxicity (Jolibois and Guerbet, 2005b). However, for other hospitals and other wastewater treatment plants, it is not obvious that the genotoxic contamination disappears after treatment in the wastewater treatment plant, and thus this contamination could be found in drinking water (Waters et al, 1989;Doerger et al, 1992;Filipic and Toman, 1996). Since hospitals are one of the sources of rejections of genotoxic compounds in wastewater, efforts must be undertaken by hospitals in order to integrate the 195 Hospital wastewater genotoxicity knowledge and the control of their wastewaters, and thus the environment management, in the infection and environmental control programs.…”
Section: Resultsmentioning
confidence: 99%
“…The observed S9 effect on sewage treatment effluents was very minor. While Hopke et al [1984] demonstrated that S9 can decrease the mutagenicity of municipal waste water sludge, Waters et al [1989], Meier et al [1987], and Brown and Donnelly [1988] reported an increase in mutagenicity in the presence of S9. Five of the 12 samples that elicited a greater response with S9 were obtained from pulp and paper mills.…”
Section: Industry Groupmentioning
confidence: 99%
“…There is a growing concern about the genotoxicity of complex environmental mixtures as waste waters, natural waters, and surface waters used for drinking water, due to the risk of genetic damage and cancer on aquatic organisms and humans (HOFFMANN 1982;FISKESJO 1985b;DONELLY et al 1987;WATERS et al 1989;FAWELL and HORTH 1990). Most studies on the subject are carried out with XAD-concentrated samples in the Ames test (STAHL 1991).…”
mentioning
confidence: 99%